The Role of Organizational Culture in Achieving The Entrepreneurial Orientation of Organizations A field study on the General Company for Transforming Industries "kanar" - ماء البارد, نور; ميا, علي يونس; إسبر, لمى (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This study aimed to assess the prevailing organizational culture in the company under study through the following dimensions: (values, beliefs, norms and expectations), assess the level of leadership orientation available in it, and study the role of organizational culture in achieving entrepreneurial orientation. The questionnaire to collect data from the study sample, which included 75 employees from various administrative levels. To achieve this, one main hypothesis was formulated from which four sub-hypotheses were derived, and the researcher reached several results, the most important of which are: The company under study does not have the organizational culture necessary to enhance employee loyalty and belonging to his work, and the company under study does not adopt a pioneering approach that enhances its ability to find alternative solutions The problems it faced as soon as possible, as the study company did not adapt flexibly to the emergency changes, which affected the results of its work, and there is no statistically significant relationship between each of the values, beliefs, organizational norms and entrepreneurial orientation in the company under study, while there is a statistically significant relationship between Organizational expectations and entrepreneurial orientation in the company under study, but it is a very weak relationship. There is a statistically significant relationship between organizational culture and entrepreneurial orientation in the company under study, but it is a very weak relationship.